Konflik Perbatasan Indonesia Dengan Republic Democratic of Timor Leste di Wilayah Distrik Oecusse - Patrianus Lela; Juan Sebastian Wodo; Yohanes Arman (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The border conflict between Indonesia and the democratic republic is the problem raised by the author. This research was conducted with the aim of finding out how the socio-economic conditions of people living in border areas and what is the legal basis for determining boundaries. The method used for this research is a qualitative research method, with a technique data collection through interviews, desk studies. The results of the research also show that the people who live on the border are on average including low-income people; in areas close to the border line in RDTL are settlements, while in Indonesia it is in the form of forests where the community does not manage; In determining the border line does not involve the local community.